Changes in the Physical Environmental Conditions of the Class C Material Mining Area in the Wayori River, Negeri Passo, Baguala District, Ambon City - Farneubun, Yakobus Riskal; Salakory, Melianus; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The Environment encompasses the entire complexity of space involving natural elements, resources, energy, conditions, and living things, including the role of humans and their behavior, which directly or indirectly impact nature, survival, human welfare, and other living things. In this context, the physical Environment becomes a concrete aspect of natural and artificial elements. The natural Environment involves land, rivers, floodplains, slopes, water bodies, soil, and vegetation. At the same time, the built Environment includes physical structures, public infrastructure, and other artificial elements. This study uses survey methods and samples from the mining worker population to focus on the impact of mining activities for class C materials in the Wayori River, Negeri Passo, Baguala District, Ambon City. The study's results highlight that changes in physical environmental conditions in mining areas can significantly impact ecosystems and human health. Unprotected land is susceptible to erosion, threatening soil quality, and potentially detrimental to agricultural land in the future. In addition, mining activities can also affect the population of soil microorganisms that are important for plant nutrients, potentially affecting plant life indirectly. The conclusions of this study provide an in-depth understanding of the complex relationships between human activities, especially mining, with the physical Environment and their implications for ecosystem and environmental health.